Depresi Dan Pencapaian Akademik Remaja Dari Keluarga Berbeza Struktur - Yaacob, Siti Nor; Abdul Rahman, Anita (Penerbit Universiti Sains Malaysia, 1997)
This study compared adolescents from single-parent and two-parents families with respect to depression and academic achievement. The data are based on a self-administered questionnaire distributed to 112 selected secondary school students. The statistical methods utilized are t-test and pearson correlation. Results show that adolescents from single-parent families obtained higher depression scores and lower academic achievement scores than adolescents from two-parent families. Additional analyses show significant differences between girls from single-parent and two-parent families for both variables examined. Depression was not significantly correlated with academic achievement among adolescents.